FUNGSIONALITAS DAN EFISIENSI RUANG BACA DI TERMINAL DUNGINGI KOTA GORONTALO DENGAN PENDEKATAN “SMART BUILDING” - Ajami, Frans Mitran; Bakari, Zulkifli (Architecture Study Program, Faculty of Engineering, Madako University Tolitoli, 2024)
Indonesia is a country with very low reading interest. Technological developments can be utilized to change lazy reading habits into reading hobbies through interactive features such as highlighting, digital notes, and automatic recommendations to make the reading experience more interesting and personal. With advanced technology, someone can read anywhere and anytime, including while waiting, which is often an unproductive time. This study uses a qualitative method with an architectural approach to understand aspects of space, design approaches, and human interaction with the built environment. The research location is focused on the Dungingi Terminal, Gorontalo City, the data includes primary and secondary, data collection techniques using observation techniques, interviews, surveys, and documentation. Data analysis uses data display, data grouping, data reduction, and data interpretation. The results of the study indicate that re-growing people's interest in reading does not need to be in a library building, but it can also be done in public buildings, so that increasing lumeration and literacy in the community goes well. In the reading room with an architectural approach concept with